Crosstalk between bile acids and gut microbiota: a potential target for precancerous lesions of gastric cancer - Zhang, Maofu; Zhong, Jialin; Shen, Yanyun; Song, Zhongyang (Frontiers in Pharmacology, 2025)
As a critical juncture in the pathological continuum from gastritis to gastric cancer, precancerous lesions of gastric cancer (PLGC) are increasingly prevalent, significantly undermining the health of the global population. The primary constituents of bile, specifically bile acids (BAs), disrupt the equilibrium of gastric hormone secretion and compromise the structural integrity of the gastric mucosa, thereby facilitating gastric oncogenesis. Moreover, gut microbiota modulate host physiological and pathological processes through immune response regulation, metabolic pathway interference, and direct interaction with gastric tumor cells. Extensive research has elucidated that the metabolic dysregulation of BAs and gut microbiota, in concert with the resultant impairment of the gastric mucosa, are central to the pathogenesis of PLGC. In anticipation of future clinical preventive and therapeutic strategies, this review collates recent insights into the roles of BAs and gut bacteria in PLGC, examining their interplay and significance in the pathogenic mechanism of PLGC.